Analysis of Triacylglycerols and Free Fatty Acids in Algae Using Ultra-Performance Liquid Chromatography Mass Spectrometry - Samburova, Vera; Lemos, Mark S.; Hiibel, Sage; Kent Hoekman, S.; Cushman, John C.; Zielinska, Barbara (Journal of the American Oil Chemists' Society, 2013)
To assess the suitability of microalgal strains for biodiesel production the lipid content and composition, especially individual triacylglycerols (TAG) and free fatty acids (FFA) must be determined. In this study, the compositions and concentrations of TAG and FFA were analysed in four halophytic algal species, Dunaliella salina , D. tertiolecta , D. bardawil , and D. granulata . These species were selected as part of a larger screen to identify species suitable for biofuel feedstocks. An accelerated solvent extraction instrument was used for lipids and fatty acid extraction using a dichloromethane–hexane solvent system. Ultra-performance liquid chromatography coupled with mass spectrometry (MS) detection was optimized and applied to the quantitative analysis of TAG and FFA in the different algal extracts. Individual TAG were characterized structurally using direct electrospray ionization (ESI) MS and MS/MS techniques. Cationic adducts (NH 4 + ) of TAG were detected and quantified in the positive ESI MS and MS/MS modes, while the negative ESI mode was used for FFA analysis. Over 20 TAG were identified and quantified in the four Dunaliella strains. Analysis of FFA compositions demonstrated that the most abundant FFA in these four algal species were palmitic, linolenic, linoleic, and oleic acids.